Characteristics of drug safety alerts issued by the Spanish Medicines Agency - Eva Montané; Eva Montané; Javier Santesmases; Javier Santesmases (Frontiers Media S.A., 2023)
Objectives: To describe the characteristics of safety alerts issued by the Spanish Medicines Agency (AEMPS) and the Spanish Pharmacovigilance System over a 7-year period and the regulatory actions they generated.Methods: A retrospective analysis was carried out of drug safety alerts published on the AEMPS website from 1 January 2013 to 31 December 2019. Alerts that were not drug-related or were addressed to patients rather than healthcare professionals were excluded.Results: During the study period, 126 safety alerts were issued, 12 of which were excluded because they were not related to drugs or were addressed to patients and 22 others were excluded as they were duplications of previous alerts. The remaining 92 alerts reported 147 adverse drug reactions (ADRs) involving 84 drugs. The most frequent source of information triggering a safety alert was spontaneous reporting (32.6%). Four alerts (4.3%) specifically addressed health issues related to children. ADRs were considered serious in 85.9% of the alerts. The most frequent ADRs were hepatitis (seven alerts) and congenital malformations (five alerts), and the most frequent drug classes were antineoplastic and immunomodulating agents (23%). Regarding the drugs involved, 22 (26.2%) were "under additional monitoring." Regulatory actions induced changes in the Summary of Product Characteristics in 44.6% of alerts, and in eight cases (8.7%), the alert led to withdrawal from the market of medicines with an unfavorable benefit/risk ratio.Conclusion: This study provides an overview of drug safety alerts issued by the Spanish Medicines Agency over a 7-year period and highlights the contribution of spontaneous reporting of ADRs and the need to assess safety throughout the lifecycle of medicines.